Entrepreneurship Education at All Levels of Education: A Systematic Literature Review - Liszt-Rohlf, Verena; Büker, Ronja; Kamsker, Susanne (21th Biennial EARLI Conference)

Vernetzte Musikquellen des 19. Jahrhunderts. Überlegungen zum Zusammenspiel wissenschaftlicher Editionen mit RISM am Beispiel des Stuttgarter Faust 1832 - Frömmel, Lena; Münzmay, Andreas (Musikquellen des 19. Jahrhunderts in Deutschland. Herausforderungen und Chancen)
This article explores the challenges and opportunities of documenting and cataloguing 19th-century music sources in Germany, using the 1832 Stuttgart production of Goethe’s Faust with music by Peter Joseph von Lindpaintner as a case study. The main focus lies on the potential interplay between (digital) critical music editions and RISM as complementary approaches to source documentation. While RISM has traditionally concentrated on pre-1800 sources, the vast and complex landscape of 19th-century music-theatrical materials—especially handwritten performance materials, but also printed sources—calls for new collaborative strategies. Drawing on the Faust edition within the OPEN Edirom project, which publishes data in open, structured formats (TEI and MEI) and makes them accessible via the RADAR4Culture repository and the Culture Knowledge Graph, the article argues for closer integration between editorial projects and RISM through stable identifiers and Linked Open Data principles. Editorial descriptions do not compete with RISM records but meaningfully extend them, and vice versa. The case study illustrates how editorial source descriptions and full-text editions could enhance the informational scope and augment the reach of RISM, and how RISM could serve as a basis for more granular, interconnected, and FAIR-compliant musicological research infrastructures. The article proposes RISM as a central access point for distributed research data and outlines the simple yet effective steps researchers can take to enhance discoverability and interoperability: namely, by using (or if necessary, creating) RISM IDs and by publishing data with persistent Digital Object Identifiers (DOIs).

Jitter in photon-number-resolved detection by superconducting nanowires - Sidorova, Mariia; Schapeler, Timon; Semenov, Alexej D.; Schlue, Fabian; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Bartley, Tim (APL Photonics)
By analyzing the physics of multi-photon absorption in superconducting nanowire single-photon detectors (SNSPDs), we identify physical components of jitter. From this, we formulate a quantitative physical model of the multi-photon detector response that combines the local detection mechanism and local fluctuations (hotspot formation and intrinsic jitter) with the thermoelectric dynamics of resistive domains. Our model provides an excellent description of the arrival-time histogram of a commercial SNSPD across several orders of magnitude, both in arrival-time probability and across mean photon number. This is achieved with just three fitting parameters: the scaling of the mean arrival time of voltage response pulses, as well as the Gaussian and exponential jitter components. Our findings have important implications for photon-number-resolving detector design, as well as applications requiring low jitter, such as light detection and ranging (LIDAR).
Keywords: Jitter; PNR; SNSPD

Peter Joseph von Lindpaintner, Ouverture, Entreacte, Chöre und Lieder zu Goethes Faust nach der szenischen Einrichtung von Carl Seydelmann (1832)
The present OPEN Edirom digital edition of Goethe’s Faust presents the literary and musical text of the work as it was possibly performed at its premiere (Friday, March 2, 1832) and consecutive performances under the direction and participation of Carl Seydelmann (directing the production and playing the role of Mephistopheles) and Peter Joseph von Lindpainter in the Stuttgart Hoftheater in 1832 (March 11, May 28, October 12) and 1833 (May 14, December 27), in accordance with the surviving sources, i.e., the original theatre material preserved in the Württemberg State Library in Stuttgart (D-Sl). This material constitutes a nearly complete autograph source package consisting of text adaptation (an autograph by Seydelmann incorporated into a copy of the print edition published by Cotta in Tübingen in 1830) and corresponding music (two volumes with autograph scores by Lindpaintner).

Mit KI (Elicit) den Forschungsstand beschreiben – ein kritischer Erfahrungsbericht - Schmidt, Rebecca (Sozialwissenschaftliche Methodenberatung)

Participatory Research with Teachers - A Critical Analysis of Power Dynamics - Schmidt, Rebecca (Transdisziplinäre Räume in den Kulturwissenschaften)

Aufruhr im Raum der Räume: Logik zwischen Philosophie und Mathematik - Peckhaus, Volker (Transdisziplinäre Räume in den Kulturwissenschaften)

Eckes, Christophe, “Philosophical and Mathematical Duality in Albert Lautman’s Work”, in: R. Krömer und E. Haffner (Hgg.), Duality in 19th and 20th Century Mathematical Thinking, Cham: Birkhäuser 2024 (Science Networks. Historical Studies; 63), 435–469. - Peckhaus, Volker (zbMATH Open, Zbl. 07951350)

Krömer, Ralf, “The Historical Development of Pontrjagin Duality”, in: R. Krömer und E. Haffner (Hgg.), Duality in 19th and 20th Century Mathematical Thinking, Cham: Birkhäuser 2024 (Science Networks. Historical Studies; 63), 291–353. - Peckhaus, Volker (zbMATH Open, Zbl. 079505172)

Krömer, Ralf, “The Historical Development of Pontrjagin Duality”, in: R. Krömer und E. Haffner (Hgg.), Duality in 19th and 20th Century Mathematical Thinking, Cham: Birkhäuser 2024 (Science Networks. Historical Studies; 63), 291–353. - Peckhaus, Volker (zbMATH Open, Zbl. 07951348)

Corry, Leo, “Von Neumann and Impossibility, from Gödel to EDVAC”, in: Mastering the History of Pure and Applied Mathematics – Essay in Honor of Jesper Lützen (De Gruyter Proc. Math.), De Gruyter. Berlin 2024, 75–99. - Peckhaus, Volker (Mathematical Reviews, MR4769331)

Costantini, Filippo, “Definitions by Abstraction and Leibniz’s Notion of Quantity”, Theoria 90 (2024), 240–255. - Peckhaus, Volker (Mathematical Reviews, MR4740767)

Robust and Efficient Hybrid Optimal Control via Gaussian Process Regression and Multiple Shooting With Experimental Validation on a Double Pendulum on a Cart - Hesse, Michael; Schwarzer, Luis; Timmermann, Julia; Trächtler, Ansgar (PAMM)
ABSTRACT In this contribution, we propose an innovative method for determining optimal control sequences for nonlinear systems with partially unknown dynamics, which further expands our previous work. Within the paradigm of model‐based design, the practicality and safety of commissioning feedforward controls and feedback controllers have priority. Our approach leverages probabilistic Gaussian processes to adjust for model inaccuracies from measured system data. This differs from conventional approaches that involve complicated analytical modeling and may entail a substantial time investment to acquire expertise and may prove impractical. Consequently, we address the limitations inherent in traditional design methodologies. Our research focuses on the formulation and solution of the hybrid 1 optimal control problem using probabilistic state predictions and multiple shooting. This ensures adaptability, data efficiency, and resilience against uncertainties in system dynamics. These attributes are empirically substantiated through experimental validation on a chaotic and highly sensitive dynamical system—a double pendulum on a cart. Our methodology unfolds as an iterative learning process, systematically exploring diverse controls, accumulating data within each iteration, and refining the control strategy until the desired task is accomplished. The adoption of the two‐degree‐of‐freedom control structure allows for the distinct consideration of the feedforward and the feedback control signal. For the latter, we employ a time‐variant, linear quadratic regulator (LQR) designed to stabilize the system around its target trajectory. Furthermore, we integrate a probabilistic long‐term prediction through the unscented transform, enabling systematic anticipation of safety‐critical violations. Detailed insights into relevant implementation aspects are provided. To ascertain the real‐world applicability, we present an exemplary application involving a double pendulum on a cart. The objective is to bring the pendulum arms from the lower stable to the upper unstable equilibrium by horizontally moving the cart and subsequently stabilize them. In this scenario, we assume that the centrifugal forces, crucial to the system dynamics, have not been accurately modeled and must be learned from data. Solving the control task took only 5 iterations and 1 h of computation time, which surpasses our previous work [2], where we used the purely data‐driven PILCO framework and required 27 iterations and 57 h of computation time. The time of interaction with the system decreased by and the computation time is lowered by . It demonstrates significant practical applicability for commissioning control systems.

Bolzano, Bernard, Miscellanea mathematica 22, hg. v. Jan Berg, besorgt von Edgar Morscher und Otto Neumaier, Frommann-Holzboog: Stuttgart-Bad Cannstatt 2024 (Bernard Bolzano-Gesamtausgabe; II.B.12.2) - Peckhaus, Volker (zbMATH Open, Zbl. 07963874)

studiVEMINT Mathematik-Online-Vorkurs jetzt mit 300 integrierten Lernvideos frei verfügbar - Biehler, Rolf; Liebendörfer, Michael; Schmitz, Angela; Reich, Birte (Mitteilungen der Deutschen Mathematiker-Vereinigung)

Research Directions in Software Supply Chain Security - Williams, Laurie; Benedetti, Giacomo; Hamer, Sivana; Paramitha, Ranindya; Rahman, Imranur; Tamanna, Mahzabin; Tystahl, Greg; Zahan, Nusrat; Morrison, Patrick; Acar, Yasemin; Cukier, Michel; Kästner, Christian; et al. (ACM Transactions on Software Engineering and Methodology)
Reusable software libraries, frameworks, and components, such as those provided by open source ecosystems and third-party suppliers, accelerate digital innovation. However, recent years have shown almost exponential growth in attackers leveraging these software artifacts to launch software supply chain attacks. Past well-known software supply chain attacks include the SolarWinds, log4j, and xz utils incidents. Supply chain attacks are considered to have three major attack vectors: through vulnerabilities and malware accidentally or intentionally injected into open source and third-party dependencies/components/containers ; by infiltrating the build infrastructure during the build and deployment processes; and through targeted techniques aimed at the humans involved in software development, such as through social engineering. Plummeting trust in the software supply chain could decelerate digital innovation if the software industry reduces its use of open source and third-party artifacts to reduce risks. This article contains perspectives and knowledge obtained from intentional outreach with practitioners to understand their practical challenges and from extensive research efforts. We then provide an overview of current research efforts to secure the software supply chain. Finally, we propose a future research agenda to close software supply chain attack vectors and support the software industry.

Smart Home Users’ Security and Privacy Perceptions and Actions Differ By Device Category: Results from a U.S. Survey - Haney, Julie M.; Acar, Yasemin; Li, Anna; Haney, Faith (Lecture Notes in Computer Science)

"It’s Time. Time for Digital Security.": An End User Study on Actionable Security and Privacy Advice - Rotthaler, Anna Lena; Ramulu, Harshini Sri; Simko, Lucy; Fahl, Sascha; Acar, Yasemin (IEEE Symposium on Security and Privacy, SP 2025, San Francisco, CA, USA, May 12-15, 2025)

More than Usability: Differential Access to Digital Security and Privacy - Buckmann, Annalina; Nold, Jan Magnus; Acar, Yasemin; Zou, Yixin (Twenty-First Symposium on Usable Privacy and Security, SOUPS 2025, Seattle, WA, USA, August 10-12, 2025)

S3C2 Summit 2024-09: Industry Secure Software Supply Chain Summit - Rahman, Imranur; Acar, Yasemin; Cukier, Michel; Enck, William; Kastner, Christian; Kapravelos, Alexandros; Wermke, Dominik; Williams, Laurie